Development of Physics Teaching Materials Based on Local Wisdom to Improve Students' Critical Thinking Skills - Andi Musniar; Kaharuddin Arafah; Pariabti Palloan (Postgraduate, University of Mataram, 2025)
This type of research is Research and Development (R&D). Development is carried out by referring to the 4D model. This study aims to produce local wisdom-based teaching materials to improve students' critical thinking skills that meet valid and practical criteria, analyze the effectiveness of using local wisdom-based teaching materials to improve students' critical thinking skills that have been developed. The results of the study showed that expert research on local wisdom-based teaching materials that had been developed was then analyzed using the Aiken'V formulation, obtained an average aspect of content feasibility of 0.86, presentation feasibility of 0.90, and language aspect of 0.81 and stated that it met the feasibility criteria (valid). The results of the teacher's assessment of the teaching materials obtained aspects of the feasibility of instructions with an average of 3.83, aspects of the coverage of questionnaire components of 3.67, and aspects of language feasibility of 3.44 with a very practical category. So, it can be concluded that this local wisdom-based teaching material is declared feasible to be tested. The effectiveness of local wisdom-based teaching materials can be seen from the increase in students' critical thinking skills based on the results of the pretest and posttest which were analyzed using the N-Gain test. Overall, the average N-Gain value of students in critical thinking skills was 0.55 in the moderate category. So it can be concluded that there is an increase in the critical thinking skills of class XI students of SMAN 14 Bone. This shows that local wisdom-based teaching materials are effective for use in the learning process.